Whole Genome Microarray Analysis of Gene Expression in an Imprinting Center Deletion Mouse Model of Prader–Willi Syndrome - Bittel, Douglas C. (Am J Med Genet A, 2007)
Prader–Willi syndrome (PWS) is caused by loss of paternally expressed genes in the 15q11-q13 region. To further characterize alterations in gene expression in this classical obesity syndrome we used whole genome microarrays to study a PWS mouse model resulting from a paternally derived imprinting center (IC) deletion (PWS IC deletion). These mice die generally within 2–3 days of life (reflective of failure to thrive in infants with PWS) and therefore, the analysis was performed on RNA extracted from the whole brain of PWS IC deletion mice and normal littermates at less than 24 hr after birth. Of more than 45,000 probes examined, 26,471 (59%) were detected for further analysis, and 69 had a significant change in expression of at least 1.5-fold and a false discovery rate (FDR) of 5%. Eight of the genes with differential expression were imprinted and from the PWS critical region (PWSCR). The three genes with the highest expression in the PWS IC mice were pro-opiomelanocortin (Pomc) and two transcripts of unknown function. Pomc knockout mice have been shown to develop obesity. Therefore, elevated Pomc RNA in PWS IC deletion neonatal mice may be an important genetic factor in the survival of these mice as it may affect eating behavior. Interestingly, Mc5r, a melanocortin receptor known to directly respond to Pomc expression changes, was upregulated as well. Mc5r is known to be involved with thermoregulation which is reportedly abnormal in PWS infants. These observations support a role for Pomc and the network of genes involved in regulating energy homeostasis in the early clinical findings of failure to thrive observed in PWS. Other notable patterns include three previously unstudied transcripts that are expressed only from the paternal allele under regulatory control of the IC and include AK013560, BB3144814, and BB182944 (whose genes are located in the mouse PWSCR on chromosome 7B). As expected, all the known paternally expressed genes from the PWSCR had detection signals below the threshold in the PWS IC deletion mice but were clearly detectable in control littermates. Several of the genes in this study were further examined by quantitative reverse transcription-PCR (RT-PCR) to confirm their expression status. Further analysis of gene expression in these mice may lead to novel pathways affected in PWS. These results, along with other recent reports, suggest that the cumulative effect of modest changes in expression of many genes, especially genes involved in energy metabolism, contribute to the failure to thrive of infants with PWS.